DRUG-ADDICTS AND THE PANDEMIC COVID-19: A STUDY OF THE COMMUNICATION PATTERNS IN SELECTED DE-ADDICTION CENTERS OF PUNJAB - Nidhi Sharma , Dr. Fakira Mohan Nahak (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Punjab is one of the Indian states where drug addiction problem has become a concern for one and all. Almost majority part of the entire state is affected by drug addiction. Youth have continuously been trapped in the cobweb of drugs and because of that, their families have been totally ruined economically, socially and psychologically. Despair and mental agony loom large in their families. Consequently, their communication structure with their sons or daughters has gone totally haywire. Beside that in the situation of Corona virus pandemics, drug addicts are living in fear with their families. In this paper, the researchers have discussed communication pattern of drug addicts including their affected life style, family history, role of media and social environment as well as verbal communication between drug addicts and their family members in special condition of COVID-19 pandemics. How the environment including all channels of media creating knowledge and fear among drug addicts have been discussed here with empirical evidence. The basic objectives of the study encircle the role of interpersonal communication of drug addicts with their family members and the role of media in present scenario. The interview method has been used to conduct research and schedule as a tool to assemble data from selected drug de-addiction centers. The present study has been conducted on 100 male and female samples having the age group between 15-40 years. The area of this study is the Doaba region of Punjab which includes 4 districts Hoshiarpur, Jalandhar, Kapurthala and Shaheed Bhagat Singh Nagar. Researchers have selected 2 drug de-addiction centers from selected districts. Accessibility to the families of drug addicts and female drug addicts section are very limited. The study is an attempt to find out that media should play an effective role as watchdog among drug addicts in present scenario. Government and media should take necessary steps to create open communication environment to eradicate this problem. Along with this separate effective policy for drug addicts to cover up gap of knowledge and fear of COVID-19.